The Effectiveness of Population Service Innovation Through the Pecel Breakfast Program in Madiun Regency - Susul Setiono; Dandy Wirawan; Zainal Fatah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Public services in the digital era demand a more responsive and inclusive bureaucratic transformation to fulfill citizens' basic rights in population administration. In Madiun Regency, geographical constraints, complex bureaucracy, and low digital literacy are major challenges in service accessibility. In response, the Population and Civil Registration Office launched the